Analysis of Product Development in Efforts to Increase Coffee Sales Volume - Mukhlis, Mukhlis; Mukhsin, Zainuddin; Wahyuni, Wahyuni (Universitas Negeri Semarang, 2021)
This study aimed to analyze the effect of product development on sales volume at UD. HASYIMAH Potu Village, Dompu Regency. This study used a quantitative approach. The subjects in this study were 40 consumers who were taken based on random sampling techniques and were selected as members of the sample who were then given a questionnaire to measure their perceptions. Based on the results of the data analysis above, it showed that the average value of the respondents’ answers can be concluded that the product development of Jati Piri Jatiwangi company was quite high with an average of 3.476 while the level of sales volume was quite high, namely at 3.5119. While the results of the calculation of regression coefficients explaining the influence of the independent variable on product development were quite high, namely the product development regression coefficient value was 0.752. The results of the calculation of the correlation value of product development on sales volume in this study were quite large, amounting to 0.736 or 73.6%, while the results of the determination coefficient were 0.541 or 54.1% explaining the role of product development independent variables in influencing sales volume while the remaining 45.9 % was influenced by other variables. The t-test results showed the t-value value of 6.866 > so that Ho rejected and accepted Ha which states that there is an influence between product development on an increase in sales volume.